2019
DOI: 10.2298/fil1909771m
|View full text |Cite
|
Sign up to set email alerts
|

On concomitants of ordered random variables under general forms of Morgenstern family

Abstract: Based on the extensions of Morgenstern family (Huang and Bairamov extensions), the concomitants of different types of generalized order statistics (os) and dual generalized order statistics (d os) are obtained. Moreover, a unified approach to such models is derived. Information properties such as Shannon entropy and Kullback-Leibler divergence for Huang and Kotz extension are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Moreover, we concluded that the suggested estimators are influenced by sample size and almost give the same behavior in the simulation procedure. In future work, we can extend the obtained models for ordered variables and their concomitants, for more details see [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we concluded that the suggested estimators are influenced by sample size and almost give the same behavior in the simulation procedure. In future work, we can extend the obtained models for ordered variables and their concomitants, for more details see [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we can apply those models to ordered variables and their concomitants for future work. For more details, see [ 17 , 18 , 19 ]. For applications, see [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they have almost the same value. In future work, we can extend this work to various types of measures such as Tsallis entropy; for more details, see [18] , [19] , [20] , [21] , [22] , [23] , [24] .…”
Section: Discussionmentioning
confidence: 99%